A Simple Finite Element Method for the Reissner-Mindlin Plate (Journal of Computational Mathematics, 1994)
A simple finite element method for the Reissner-Mindlin plate model in the primitive variables is presented and analyzed. The method uses conforming linear finite elements for both the transverse displacement and rotation. It is proved that the method converges with optimal order uniformly with respect to thickness. It is simpler and more economical than the Arnold-Falk element.